透過型電子顕微鏡（TEM）によるセラミックス材料の微構造観察と解析 - 中野, 裕美 (Funtai Kogakkaishi, 2017)
Microstructural observation using transmission electron microscopy (TEM) is a promising technique for obtaining new findings with atomic-scale and developing phenomenological theory for ceramic materials. This paper reports on observation techniques and diverse findings obtained by observations of several ceramics. The knowledge obtained here is expected to be useful in the design of future materials.